Dihydroquercetin Attenuates Silica-Induced Pulmonary Fibrosis by Inhibiting Ferroptosis Signaling Pathway - Yuan, Leyong; Sun, Yan; Zhou, Ning; Wu, Weipeng; Zheng, Weidong; Wang, Yukun (Frontiers in Pharmacology, 2022)
Silicosis is a fatal occupational lung disease which currently has no effective treatment. Dihydroquercetin (DHQ) is a flavonoid compound known for its anti-inflammatory, anti-oxidant and anti-cancer bioactivity. However, whether DHQ protects against silica-induced lung fibrosis remains unknown. Therefore, we aimed to investigate the effect of DHQ on silica-induced lung fibrosis and the underlying molecular mechanism in vivo and in vitro. Our results demonstrated that DHQ treatment markedly attenuated SiO2-induced inflammation and fibrosis degree of lung tissues in the C57BL/6 mice. Additionally, experiments in vitro also confirmed that conditioned medium from DHQ-treated human bronchial epithelial (HBE) cells significantly decreased expression of fibrosis markers of human fetal lung fibroblast cells (MRC-5), such as α-SMA, collagen1 and fibronectin. Interestingly, HBE cells treated by DHQ showed few morphological features of ferroptosis compared with SiO2-treated cells. Furthermore, DHQ treatment remarkably inhibited ferroptosis in activated HBE cells by decreasing the accumulation of iron and lipid peroxidation products, and increasing levels of glutathione (GSH) and glutathione peroxidase 4 (GPX4), whereas stimulation of ferroptosis by specific inducer erastin deeply impaired anti-fibrosis effect of DHQ in vitro. More importantly, our results showed that DHQ also evidently suppressed ferritinophagy by down-regulation of microtubule-associated protein 1A/1B-light chain 3 (LC3), and up-regulation of ferritin heavy chain 1 (FTH1), nuclear receptor co-activator 4 (NCOA4) in activated HBE cells. Nevertheless, activation of ferritinophagy by specific inducer rapamycin (Rapa) evidently blocked DHQ-inhibited HBE cells ferritinophagy and anti-fibrosis effect of DHQ. Overall, our research revealed that inhibition of ferritinophagy-mediated HBE cells ferroptosis was responsible for DHQ to ameliorate SiO2-induced lung fibrosis, which provided a preliminary theoretical basis for the clinical application of DHQ in the treatment of silicosis.